Aesthetical aspects and historical significance of architectural ornament Iznik: Hermeneutical study - Zahra, Fatima (Вестник Томского государственного университета. Культурология и искусствоведение)
This article aimed to examine the aesthetical aspects and historical significance of the Iznik ornament. Iznik ornament usually referred to the floral tulip pattern, a traditionally Ottoman arabesque pattern with Chinese elements. An ornament is a form of decorative detail and gives the imagery of grandeur when associated with architecture. Moreover, an ornament can be the decorative identification of the structure in any architecture. The aesthetical aspects discuss the journey of Iznik from ceramics to architectural ornament, while historical significance explores the mythologies and concepts associated with Iznik ornament. Furthermore, the study employed a hermeneutics approach for the interpretation of the architectural ornament. The findings show that originally, Iznik ornament was only a decorative purpose though today's architecture came up with many ways and ideas to make this ornament valuable and pleasing.